The Effect Of Global Stock Price Index And Rupiah Exchange Rate On Idonesian Composite Stock Price Index (CSPI) In Indonesian Stock Exchange (IDX) - Damajanti, Anita; Yulianti, Yulianti; Rosyati, Rosyati (Economics and Business Solutions Journal, 2018)
Indonesian capital market through the Indonesia Stock Exchange is an integral part of the global stock exchange activities. The closer the relationship between Indonesian stock exchange and global stock exchanges is represented by the relationship between the stock price index. Composite Stock Price Index (CSPI) movement in Indonesia Stock Exchange has decreased for 2 (two) first quarter in 2018. This aim of this study to examine the effect of the global stock price index represented by the Dow Jones index, the Nikkei 225 Index, the Hang Seng Index and rupiah exchange rate against CSPI movement. The observation period uses daily data from 2 January to 31 August 2018. Samples are selected by using judgment sampling method, by taking the stock price index and rupiah exchange rate announced on the same day by all exchanges. There are 145 data samples and was analyzed by using linear regression. The results partially show that Hang Seng index and rupiah exchange rate have a significant effect on the CSPI, while   Dow Jones index and the Nikkei 225 Index have no significant effect on the CSPI. Simultaneously all variables have a significant effect on the CSPI. The results of goodness of fit model examination show the ability of the independent variable in explaining the dependent variable is 40.3%, while 59.7% is explained by variables outside the model.